Determination of Tetracyclines and Their Epimers in Agricultural Soil Fertilized with Swine Manure by Ultra-High-Performance Liquid Chromatography Tandem Mass Spectrometry - Wen-li ZHENG; Li-fang ZHANG; Ke-yu ZHANG; Xiao-yang WANG; Fei-qun XUE (Journal of Integrative Agriculture, 2012)
A rapid, sensitive and specific ultra-high-performance liquid chromatography tandem mass spectrometry (UPLC-MS) method was developed for the analysis of tetracycline antibiotics, including tetracycline (TC), oxytetracycline (OTC), chlortetracycline (CTC) and their 4-epimers (4-epiTCs) in agricultural soil fertilized with swine manure. Soil samples were extracted and cleaned-up with 10 mL EDTA-McIlvaine buffer solution (pH 4.0), then cleaned-up and pre-concentrated using the Oasis MAX cartridge and then eluted with 1 mL solution by mixing formic acid, methanol and water at a ratio of 2:15:83 (v/v/v). The purified samples were separated by an ACQUITY UPLC BEH C18 column using acetonitrile and water containing 0.1% formic acid mobile phase and detected by a single quadrupole MS. The limits of detection for the soil extraction method (LODsoil) ranged from 0.6-2.5 μg kg−1 with recoveries from 23.3-159.2%. Finally, the method was applied to an agricultural field in an area with intensive pig-fattening farming. Tetracyclines were detected in soil from 2.8 to 42.4 μg kg−1 soil. These results demonstrate that soil from swine farms can become severely contaminated with tetracycline antibiotics and their metabolites.